Using polyethylene sleeves with forced aeration for composting olive mill wastewater pre-absorbed by vegetative waste. (August 2018) - Avidov, R.; Saadi, I.; Krasnovsky, A.; Medina, Sh.; Raviv, M.; Chen, Y.; Laor, Y.
Graphical abstract: Highlights: Olive mill wastewater absorbed by green waste was composted in closed sleeves. Thermophilic temp. were kept for 1 month, followed by 30–40 °C for extra 3.5 months. Oxygen levels were controlled and the system was kept aerobic. Sufficient moisture remained along the composting process. The final compost was found suitable as an ingredient in growing media. Abstract: Composting in closed polyethylene sleeves with forced aeration may minimize odor emissions, vectors attraction and leachates associated with open windrows. The present study demonstrates the use of this system for composting olive mill wastewater (OMW), the undesired stream associated with the olive milling industry. A polyethylene sleeve of 1.5-m diameter and ca. 20-m long was packed with shredded municipal green waste which was pre-soaked in OMW for 72 h. Process conditions were controlled by means of a programmable logic controller (PLC) equipped with temperature and oxygen sensors. Thermophilic temperatures (>45 °C) were maintained for one month followed by temperatures in the range of 30–40 °C, ca. 20 °C above ambient temperature, for a period of 3.5 months. Oxygen levels were controlled and the system was kept aerobic. Water content gradually decreased with sufficient levels for efficient composting. The finished compost was non-phytotoxic to Cress ( Lepidium sativum L.) in a lab bioassay. It was also found suitable as an ingredient in peat, tuff, and coir based growing media, evaluated by plant growth tests with basil and ornamental plants. The viability of this approach for disposing off OMW is much dependent on the liquid absorption capacity of the vegetative waste.